Ameloglyphics: An adjunctive aid in individual identification - Ravindrakumar Bharanidharan; Raghavendhar Karthik; A Rameshkumar; P Rajashree; K Rajkumar (Wolters Kluwer Medknow Publications, 2014)
Human identification in homicides and mass disasters has been largely possible with skeletal remains, especially teeth, when soft tissue cannot provide reliable information or has been lost. From the point of forensic dental identification especially in identifying victims of man-made disasters such as in military conflicts and wars involving multiple fatalities, there is urgent need for new and reliable methods of identification and corroboration. Various methods currently employed in forensic odontology for personal identification include comparing with ante mortem dental charts, rugoscopy, denture labelling, DNA analysis from dental pulp, bite mark analysis, etc. Recently there is growing interest in the study of enamel rod end patterns. These enamel rod end patterns are termed as tooth prints and the study of these prints is known as Ameloglyphics (amelo: Enamel, glyphics: Carvings). The tooth prints are unique, exhibiting dissimilarity both between teeth of different individuals and of the same individual. This uniqueness of the tooth print could be used as a valuable tool in forensic science for personal identification. This review highlights about the basis of using enamel rod end patterns, methods of obtaining the patterns, and delineating its sub-patterns.